VNTR2/VNTR3 genotype in the FCGRT gene is associated with reduced effectiveness of intravenous immunoglobulin in patients with myasthenia gravis. (January 2021) - Su, Shengyao; Liu, Qing; Zhang, Xueping; Wen, Xinmei; Lei, Lin; Shen, Faxiu; Fan, Zhirong; Duo, Jianying; Lu, Yan; Di, Li; Wang, Min; Chen, Hai; et al.
Background: Intravenous immunoglobulin (IVIG) has been commonly used to treat myasthenia gravis exacerbation, but is still ineffective in nearly 30% of patients. A variable number of tandem repeat (VNTR) polymorphism in the FCGRT gene has been found to reduce the efficiency of IgG biologics. However, whether the polymorphism influences the efficacy of IVIG in generalized myasthenia gravis (MG) patients with exacerbations remains unknown. Methods: The distribution of VNTR genotypes was analyzed in 334 patients with MG. Varied VNTR alleles were determined by capillary electrophoresis and confirmed by Sanger sequencing. Information of endogenous IgG levels were collected in patients without previous immunotherapy ( n  = 26). Medical records of patients who received IVIG therapy were retrospectively analyzed for therapeutic outcomes of IVIG treatment ( n  = 61). Patients whose Activities of Daily Living scores decreased by 2 or more points on day 14 were considered responders to the treatment. Results: The VNTR3/3 and VNTR2/3 genotypes were detected in 96.7% (323/334) and 3.4% (11/334) patients, respectively. Patients with VNTR2/3 heterozygosity had lower endogenous IgG levels than those with VNTR3/3 homozygosity (9.81 ± 2.61 g/L versus 12.41 ± 2.45g/L, p  = 0.016). The response rate of IVIG therapy was 78.7% (48/61). All responders and nine non-responders were VNTR3/3 homozygotes, whereas all the patients with VNTR2/3 genotypes were non-responders ( n  = 4). In patients who took IVIG treatments, endogenous IgG levels were significantly lower in non-responders compared with responders (12.93 ± 2.24 g/L versus 8.85 ± 2.69 g/L, p  = 0.006), especially in VNTR2/3 heterozygotes (7.86 ± 1.78 g/L, p  = 0.001). Conclusion: The VNTR2/3 genotype could influence endogenous IgG levels and serve as a predictive marker for poor responses to IVIG in MG patients.